Acute cadmium toxicity to sea bass, Lates calcarifer - M. Shazili, Noor A.; Masato, Izawa
The acute toxicity of cadmium was determined for sea bass,Lates calcarifer at 20 days and at 4 months of age. Bioassays were conducted using a static-with-renewal procedure. The 20-days old fish were tested at 20ppt salinity only while the influence of 5,15 and 30ppt on cadmium toxicity was investigated for 4 month old fish. The 12 day median lethat concentration )LC 50) for the 20 day old fish was 4.0mg cD/l. Acclimatization to cadmium occurred,with fish exposed to 0.32mg Cd/L and 1.0mg Cd/L surviving significantly longer in a test solution of 32mg Cd/L compared to previously unexposed fish. Cadmium toxicity was influenced by salinity. The sensitivity of 4 month old fish to cadmium increased with reducing salinity,the 96-hr LC 50's being 0.74,16.5 and 19mg Cd/L at 5,15 and 30ppt salinity respectively. As Lates calcarifer spends its first 3 years of development in euryhalline conditions and is also found in freshwaters,its early life stages may be at risk to metal pollution.